Kebijakan Internal Madrasah Dalam Memenuhi Kepuasan Orang Tua Siswa Di Madrasah Ibtidaiyah Negeri 1 Kulon Progo - Sudarman Sudarman (Al-Bidayah : jurnal pendidikan dasar Islam, 2019)
The underlying reason of the study is the importance of education in global era where parents demand that, to face the future, their children should both master science and technology and have strong religion base. To maintain trust from the society, madrasah must work hard. In the last few years, MIN 1 Kulon Progo, a madrasah (Islamic School) with the highest number of students in district Temon, has experienced a constant decrease in enrolments.   The sudy shows that student parents of MIN 1 Kulon Progo expect that students 1) worship more diligently, 2) possess better moral and personality, 3) have various skills, 4) achieve better grade, and 5) reach both academic and nonacademic achievements.To respond parents’ expectation, Madrasah issues policies such as 1) improving the students’ worship quality, 2) mending their moralsand attitude, 3) strengthening the pupils’ skills, 4) setting higherachievements, 5) raising goals both academic and non academic. The policies prove to fulfil the needs although some parents think differently. It also brought further benefit to the school as more parents send their children to MIN 1 Kulon Progo in 2018/2019 school year. The school reached the target of new students (56), and it even had to refuse some candidates.